Nature of Volatile Organic Matter in Lake Sediments as a Reflection of Paleoclimate Changes Occurring at 4 ka in the Central Qaidam Basin - Lu, Xiaohang; Zhang, Yongsheng; Yi, Lei; Ma, Zhe; Su, Weigang; Liu, Xiaobao; Han, Fengqing (Frontiers in Earth Science, 2021)
This study explores the paleoclimate changes around the 4 ka BP period in the central Qaidam Basin (QB), assessing the differences in spectral characteristics and organic composition of salt lake sediments under different climate change conditions. Sediment samples (10-m-depth profile) were collected from the middle of dry salt flats in East Taijinar Lake (China). Sediment organic matter (SOM) was assessed by Fourier transform infrared spectroscopy (FTIR) and gas chromatography-mass spectrometry (GC-MS). Results showed a significant difference in the TOC content of sediments with different lithological characteristics. A lower TOC content in salt-bearing strata was attributed to the extreme sedimentary environment with minimal exogenous inputs. FTIR spectroscopy revealed that the SOM in sediments included aliphatic C, ketones and alcohols. Sediments of salt-bearing strata generally exhibited a rise in the content of ketone C=O groups and a decrease in aliphatic C, with an equal content of alcohols compared with silty sand. Therefore, exogenous OM and the content of TOC in silty sand strata are higher than in salt-bearing strata, indicating that the paleoclimate became warmer and wetter after 4 ka BP. GC-MS analysis showed a significant difference between the phenol and aldehyde content in different strata, further indicating that the paleoclimate changed from dry to relatively warm around 4 ka BP. Seven organic compound types were identified in SOM, including aldehydes, hydrocarbons, phenols, esters, ketones, alcohols, and furans. Different strata exhibited different distributions of organic compounds, with particularly high concentrations of aldehydes in salt-bearing strata and phenols in silty sand. Correlation analysis was performed between detrital minerals and OM types in all samples. Results showed a strong positive correlation between detrital minerals and phenols and a strong negative correlation between detrital minerals and aldehydes, with a negative correlation also identified between detrital minerals and ketones. Overall, the reduction in volatile organic compounds demonstrates that the paleoclimate changed from cooler and dry to wet and warm around the 4 ka BP period in the central QB, with the carbon preference index and n-alkane values further demonstrating these results. This study also confirms the importance of volatile organic compound monitoring to assess paleoclimate changes.